Effect of Tool Parameters on Performance of Soil Disruption by Shoe Type Furrow Openers for Animal Drawn Seed Drill in Sandy Loam Soil - Kurhade, Aditya Ashokrao; Sharma, Ajay Kumar; Mathur, Ravi (Journal of Agricultural Engineering, 2010)
Shoe type furrow openers are simple in design and because of their simple low-cost construction; they are widely used in seed drills for opening the soil or placement of seed and fertilizer. The study was conducted on the soil disruption by animal drawn seed drill shoe type furrow openers to improve soil conditions in sandy loam soil using four sizes of furrow openers at four lift angles (0 degree , 5 degree , 10 degree and 15 degree ) at operational speed and depth of operation of 0.69 m/s and 0.05 m, respectively. Tool 4 gave more spoil furrow width, spoil furrow depth, crescent height, spoil area and trench area at all lift angles.